Nanoscale delivery systems for microRNAs in cancer therapy - Boca, Sanda; Gulei, Diana; Zimta, Alina-Andreea; Onaciu, Anca; Magdo, Lorand; Tigu, Adrian Bogdan; Ionescu, Calin; Irimie, Alexandru; Buiga, Rares; Berindan-Neagoe, Ioana (Cellular and molecular life sciences : CMLS, 2020)
Concomitant with advances in research regarding the role of miRNAs in sustaining carcinogenesis, major concerns about their delivery options for anticancer therapies have been raised. The answer to this problem may come from the world of nanoparticles such as liposomes, exosomes, polymers, dendrimers, mesoporous silica nanoparticles, quantum dots and metal-based nanoparticles which have been proved as versatile and valuable vehicles for many biomolecules including miRNAs. In another train of thoughts, the general scheme of miRNA modulation consists in inhibition of oncomiRNA expression and restoration of tumor suppressor ones. The codelivery of two miRNAs or miRNAs in combination with chemotherapeutics or small molecules was also proposed. The present review presents the latest advancements in miRNA delivery based on nanoparticle-related strategies.